A study on the impact of the Standard Inpatient Class (KRIS) policy on private hospitals in Central Jakarta - Handojo, Pradono; Hawadi, Lydia Freyani; Lestari, Haifa Mayang (JHeS (Journal of Health Studies), 2025)
Presidential Regulation No. 59 of 2024 on the National Health Insurance (JKN), Article 103B, the government mandated the full implementation of the Standard Inpatient Class (KRIS) policy by 2025. This regulation is expected to impact the public broadly and has generated a range of perceptions. Existing research remains fragmented, lacks focus on private hospitals, and is qualitative in nature. This study aims to evaluate the readiness and vulnerabilities of private hospitals in Central Jakarta in implementing the KRIS policy. A mixed-methods approach was used to analyse the policy's impact on bed capacity, hospital revenue, and the challenges hospitals faced in meeting the 12 KRIS criteria. The findings indicated that the KRIS policy could lead to a 21% reduction in the number of beds in private hospitals, potentially worsening the issue of healthcare access, recorded as the main complaint by Health Security Administering Body (Badan Penyelenggara Jaminan Sosial Kesehatan, abbreviated as BPJS) participants in 2021. An estimated budget of IDR 16 billion is required for KRIS compliance in private hospitals across Central Jakarta, with a projected monthly revenue loss of approximately IDR 10.8 billion. Criteria 8, 9, and 11 pertain to room density, partitions, and bathroom facilities. This study recommends adjusting the KRIS policy to account for the unique characteristics of private hospitals, which do not receive financial assistance from the government. Specifically, it suggests aligning the implementation timeline with each hospital’s capacity and readiness. In addition, the government must ensure equitable access to healthcare for all BPJS participants.